Assessment of Changes in Mass Balance of the Tuyuksu Group of Glaciers, Northern Tien Shan, Between 1958 and 2016 Using Ground-Based Observations and Pléiades Satellite Imagery - Kapitsa, Vassiliy; Shahgedanova, Maria; Severskiy, Igor; Kasatkin, Nikolay; White, Kevin; Usmanova, Zamira (Frontiers in Earth Science, 2020)
Continuous measurements of glaciological mass balance have been conducted at the Central Tuyuksu glacier, Tuyuksu group of glaciers, Ile Alatau, northern Tien Shan since 1957 showing that cumulative mass balance was negative since the 1970s. Geodetic mass balance was calculated for the 1958-1998 and 1998-2016 periods using multi-temporal digital elevation models derived from the historic photogrammetric surveys from 1958 and 1998, and the high-resolution Pleiades satellite stereo imagery from 2016. Geodetic measurements revealed the mean surface lowering of 23.2±2.2 m (0.40 ± 0.04 m a-1) and reduction in volume of (67.7±6.7)x106 m3 in 1958-2016 at the Central Tuyuksu glacier yielding a geodetic mass balance of -21.8±2.6 m w.e. Similar trends were observed at other glaciers of the Tuyuksu group which lost in total 83.4x106 m3 of ice. Mass balance annual rates have not changed significantly from 1958-1998 (-0.39±0.05 m w.e.) to 1998-2016 (-0.35±0.18 m w.e.) at the Central Tuyuksu and at other glaciers of the Tuyuksu group whose maximum elevations exceed 4000 m a.s.l. While glacier thinning intensified in the ablation zone and affected larger area in 1998-2016 extending to 3600-3700 m a.s.l., accumulation increased at higher elevations in 1998-2016. Geodetic mass balance was more negative in 1998-2016 than in 1958-1998 at the smaller glaciers with lower maximum elevations. At the Central Tuyuksu, geodetic mass balance was in close agreement with glaciological mass balance particularly in 1958-1998 when the difference between the geodetic and cumulative glaciological mass balance values did not exceed 5 %. During 1998-2016, this difference increased to 14 % with glaciological method producing more negative mass balance. This discrepancy was attributed to a systematic error introduced by the lack of stakes in the accumulation zone of Central Tuyuksu whose contribution to uncertainty increased in 1998-2016 in line with increase in accumulation. Negative mass balance of the Tuyuksu group of glaciers was attributed to continuing increase in summer temperatures and low accumulation observed in the 1970s-1980s and at the turn of the century.